Nanopharmaceuticals in Regenerative Medicine (Taylor & Francis, 2022)
The book Nanopharmaceuticals in regenerative medicine is a collective and comprehensive volume of the latest innovations in nanoscience technology for practical use in clinical, biomedicine and diagnostic arena. The term nanotechnology pops up in every segment of modern-day life. The primary aim of this book is to deliver the precise information to students, educators, technologists and researchers. A conglomerate of scientists from various research fields contributed to the chapters, giving detailed descriptions on the most recent developments of nanotechnology in the area of disease management. This book will also be useful for industrial research and development partners, start-up entrepreneurs, government policy makers and other professionals who are interested in nanomedicines.
English
Keywords: Chemistry; Materials science; Medical administration and management; Nanotechnology; Pre-clinical medicine: basic sciences; Regenerative medicine, Carbon nanotube, Block copolymers, Wound healing, Anticancer therapy, Particles used in imaging